2021
DOI: 10.1128/jvi.01386-20
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIV-1 Intron-Containing RNA in Microglia Induces Inflammatory Responses

Abstract: Chronic neuroinflammation is observed in HIV+ individuals on suppressive combination antiretroviral therapy (cART) and is thought to cause HIV-associated neurocognitive disorders. We have recently reported that expression of HIV intron-containing RNA (icRNA) in productively infected monocyte-derived macrophages induces pro-inflammatory responses. Microglia, yolk sac-derived brain-resident tissue macrophages, are the primary HIV-1 infected cell type in the central nervous system (CNS). In this study, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 79 publications
(160 reference statements)
0
21
0
Order By: Relevance
“…It remains to be established whether m 6 A modifications of HIV-1 RNA regulate innate immune responses in primary CD4 + T-cells. Moreover, recent studies suggest that HIV-1 intron-containing RNA activates innate immune signaling and IFN-I induction in primary dendritic cells, macrophages, microglia, and CD4 + T cells [48][49][50]. It is conceivable that, during chronic HIV-1 infection, multiple cellular and viral mechanisms can regulate IFN-I induction and innate immune activation in infected cells and individuals.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…It remains to be established whether m 6 A modifications of HIV-1 RNA regulate innate immune responses in primary CD4 + T-cells. Moreover, recent studies suggest that HIV-1 intron-containing RNA activates innate immune signaling and IFN-I induction in primary dendritic cells, macrophages, microglia, and CD4 + T cells [48][49][50]. It is conceivable that, during chronic HIV-1 infection, multiple cellular and viral mechanisms can regulate IFN-I induction and innate immune activation in infected cells and individuals.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Such cells could exert pressure on the host immune system, causing persistent immune activation and thus contributing to rapid disease progression. Interestingly, it was recently shown that viral protein expression is not even necessary for US RNA to cause immune activation because intron-containing HIV-1 RNA can induce innate immune signaling in diverse cell types, such as dendritic cells, macrophages, and CD4+ T cells [ 38 , 39 , 40 ].…”
Section: Us/ms Rna Ratio As a Clinical Biomarkermentioning
confidence: 99%
“…In addition, it has been demonstrated that partially spliced and unspliced HIV-1 RNAs are recognized by MAVS-dependent nucleic acid sensing pathways and mediate IFN-I responses (11,12,57). The defective mRNA sequences generated from the intragenic elements that we have characterized initiate transcription within Env and span the intron leading us to speculate that these mRNAs could be proinflammatory.…”
Section: Discussionmentioning
confidence: 99%